Résous les équations suivantes :
f) x² - 9 = 8x
g) (x - 1)² + x² = x
h) x² + x + 1 = 0
i) (2x + 5)(7 - 3x) = 9
j)18x² + 27x - 5 = 0
k) 4x² + 16 = 16x
l) x² + 9 + 6x = 0
m) 3x² - 3x - 6 = 0
J'y comprend rien. (raisonnement svp)

1

Réponses

Meilleure réponse !
  • Utilisateur Brainly
2014-03-24T20:40:04+01:00
Résous les équations suivantes :
f) x² - 9 = 8x
x²-8x-9=0
(x+1)(x-9)=0
x=-1 ou x=9

g) (x - 1)² + x² = x
x²-2x+1+x²-x=0
2x²-3x+1=0
(2x-1)(x-1)=0
x=1/2 ou x=1

h) x² + x + 1 = 0
pas de solution dans IR

i) (2x + 5)(7 - 3x) = 9
-6x²+35-15x+14x-9=0
-6x²-x+26=0
(-6x-13)(x-2)=0
x=-13/6 ou x=2

j)18x² + 27x - 5 = 0
(3x+5)(3x-1)=0
x=-5/3 ou x=1/6

k) 4x² + 16 = 16x
4x²-16x+16=0
x²-4x+4=0
(x-2)²=0
x=2

l) x² + 9 + 6x = 0
(x+3)²=0
x=-3

m) 3x² - 3x - 6 = 0

x²-x-2=0
(x+1)(x-2)=0
x=-1 ou x=2